Saturday night dirt - Weaver, Will (Farrar, Straus and Giroux, 2008)
In a small town in northern Minnesota, the much-anticipated Saturday night dirt-track race at the old-fashioned, barely viable, Headwaters Speedway becomes, in many ways, an important life-changing event for all the participants on and off the track.